2001
DOI: 10.1207/s15327949pac0701_04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of political violence on images of war and peace in the drawings of primary school children.

Abstract: Protestant primary school children (N = 181) from 3 schools representing areas in Northern Ireland with high and low political and sectarian violence, and 1 area in England with no political and sectarian violence, were asked to draw pictures of peace and war. Three hypotheses were explored: (a) Northern Irish children to a greater extent than English children would emphasise the concept of peace as the absence of war; (b) children from the high-violence area of Northern Ireland would be more likely to emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
(35 reference statements)
1
30
0
Order By: Relevance
“…With respect to Dutch children's conceptions of peace and war, Hakvoort and Oppenheimer (1999) reported a reversal of gender differences that had been previously reported in the same country by Hakvoort and Oppenheimer (1993). McLernon, Ferguson, and Cairns (1997) and McLernon (1998) found no gender differences in Northern Irish children's perceptions of peace and minor differences in their perceptions of war. It was therefore not clear whether any gender differences would be present in the development of the understanding of enemy and the emergence of enemy images.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…With respect to Dutch children's conceptions of peace and war, Hakvoort and Oppenheimer (1999) reported a reversal of gender differences that had been previously reported in the same country by Hakvoort and Oppenheimer (1993). McLernon, Ferguson, and Cairns (1997) and McLernon (1998) found no gender differences in Northern Irish children's perceptions of peace and minor differences in their perceptions of war. It was therefore not clear whether any gender differences would be present in the development of the understanding of enemy and the emergence of enemy images.…”
mentioning
confidence: 55%
“…To assess children's understanding of enemies and enemy images, the methods of free association, drawing, and interview were used. These methods have been used successfully in the assessment of enemy images in previous studies (Hesse & Poklemba, 1989;Hesse & Mack, 1991;Povrzanovic, 1997), as well as conceptions about peace and war (McLernon & Cairns, 2001;Rudenberg, Jansen, & Fridjhon, 1998;Punamaki & Suleiman, 1990). The free association method requires participants to respond with the first words that come to mind to a target word that is embedded in a series of neutral words.…”
mentioning
confidence: 99%
“…Ireland (McLernon & Cairns, 2001), but there were two major problems with this earlier research. The use of leading terms, such as "peace" or "war", contaminated the findings, i.e., it should not have been a surprise that the children drew images related to peace and war when they had been asked to draw images of peace or war.…”
Section: Discussionmentioning
confidence: 81%
“…Previous scholarship noted how concepts of peace were arguably affected by culture and the specific context of people (Haavelsrud 1970;Brock-Utne 1989;McLernon, Ferguson, and Cairns 1997;Covell 1999;Hofstede 2001). Later, cross-cultural studies also showed the interconnected character between notions of peace and war among children (Haji-Yusuf 1996;McLernon and Cairns 2001).…”
Section: Notions Of Peace and Peace Effortsmentioning
confidence: 99%